PENDIDIKAN ISLAM MASA PENJAJAHAN BELANDA DAN JEPANG - Susmihara Sus (Rihlah : Jurnal Sejarah dan Kebudayaan, 2013)
Islamic education is closely related to the Japanese colonial interdependent relationship between Japan and the Muslims. Japan needs of Muslims in Indonesia related to the Greater East Asia War, that the Japanese had help from Indonesian Muslims. While Muslims expect will acquire Indonesia's independence. Japanese colonial policy seemed a little more lenient towards Islamic education than the Dutch colonizers. Japan even offer financial assistance to madrasas, and let the public reopening madrassas are never closed by the Dutch colonial government. Determination is embedded in the chest of Muslims to the truth that is run as a supporter of the development of Islamic education, while a policy that is applied invaders an inhibiting factor. Impact of the Dutch educational system and Japan led to the emergence of the reform movement of religious thought of Islam Education Islamic leaders to keep making progress.